Use of dietary supplements by pregnant women in Colombia (2018)
Background: During pregnancy, the need for certain nutrients increases. This study assessed the prevalence and socio-demographic factors associated with dietary supplement use in a representative sample of pregnant women in Colombia. Method: Data for this study were obtained from a cross-sectional, nationally representative survey (ENSIN, 2010). A total of 1856 pregnant women, 13-49 years of age, were recruited. The use of prenatal dietary supplements (Vitamins A, C or E) was treated as a binary outcome (used at some time or never sued during pregnancy when prescribed by a doctor) in multinomial analyses. Sociodemographic data and associated factors were assessed by computer-assisted personal interview technology. Results: Of the sample, 1123 women (68.6%) reported taking prenatal dietary supplements at some stage during their pregnancy. Most users had a high socioeconomic level (79.5%), were in their third trimester of pregnancy (79.5%), were 30-49 years of age (74.0%), and lived in the central region of Colombia (73.8%). The multivariate logistic regression showed that third trimester of pregnancy (OR 6.2;95% CI 4.0 to 9.3), high educational level (OR 2.3; 95% CI 1.5 to 3.4), high socioeconomic level -SISBEN IV or more- (OR 2.0; 95% CI 1.4 to 2.8), residence in the Atlantic region (north) (OR 2.6; 95% CI 1.7 to 3.6), Eastern region (OR 2.0; 95% CI 1.3 to 3.1), central region (OR 2.6; 95% CI 1.7 to 3.9), Pacific region (west) (OR 1.5; 95% CI 1.0 to 2.3), and belonging to the mestizo (others) ethnic group (OR 1.2; 95% CI 1.0 to 2.6), were all associated with a higher probability of dietary supplement intake. Conclusion: The prevalence of prenatal dietary supplements in pregnant women in Colombia was found to be substantial. The variables significantly associated with their use were educational level, socioeconomic level, trimester of pregnancy, geographic level and ethnic group. These results indicate the necessity of implementing new health policies that guarantee uniform access to nutritional supplements for all population sectors, especially in countries, such as Colombia, who are currently undergoing a process of nutritional transition. © 2018 The Author(s).